2018
DOI: 10.1038/s41467-018-03589-y
|View full text |Cite
|
Sign up to set email alerts
|

High-capacity optical long data memory based on enhanced Young’s modulus in nanoplasmonic hybrid glass composites

Abstract: Emerging as an inevitable outcome of the big data era, long data are the massive amount of data that captures changes in the real world over a long period of time. In this context, recording and reading the data of a few terabytes in a single storage device repeatedly with a century-long unchanged baseline is in high demand. Here, we demonstrate the concept of optical long data memory with nanoplasmonic hybrid glass composites. Through the sintering-free incorporation of nanorods into the earth abundant hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…Even at ambient conditions [ 124 ], but more readily as temperature increases, and often even more conspicuously upon irradiation with short optical pulses, gold nanorods tend to reshape into rounder particles. The driver for this process is that the prolate shape originating from the anisotropic growth of gold nanorods is out of thermodynamic equilibrium and departs from their Wulff construction [ 125 , 126 ], which resembles a faceted sphere.…”
Section: Contrast Agents For Photoacoustic Imagingmentioning
confidence: 99%
“…Even at ambient conditions [ 124 ], but more readily as temperature increases, and often even more conspicuously upon irradiation with short optical pulses, gold nanorods tend to reshape into rounder particles. The driver for this process is that the prolate shape originating from the anisotropic growth of gold nanorods is out of thermodynamic equilibrium and departs from their Wulff construction [ 125 , 126 ], which resembles a faceted sphere.…”
Section: Contrast Agents For Photoacoustic Imagingmentioning
confidence: 99%
“…To date, several kinds of nanomaterials, such as metallic nanocrystals (NCs) 8,11 , graphene oxide [12][13][14] , semiconductor quantum dots [15][16][17] and rare-earth ion-doped NCs 18,19 , have been developed as ODS media, utilizing their physical and/ or chemical state variations during light-matter interactions. Despite the fascinating ODS properties, the shortcomings of high cost, tedious preparation route and low production greatly hinder their practical applications; moreover, these NCs are bound to disperse into organic hosts, which brings about a stability issue: colouration-or shrinkage-induced performance reduction under long-term repeatable laser write-in/read-out 9,[20][21][22] . Evidently, the exploration of new ODS nanomaterials to address the issues stated above is able to promote rapid progress in information preservation technology.…”
Section: Introductionmentioning
confidence: 99%
“…In optical storage, data is usually recorded by making marks in a pattern and read back using a focused laser that scans over the surface of the pattern. [233][234][235] The storage capacity, as can be imagined, depends signicantly on the size of the probe beam. PNJs generated by dielectric microspheres have been demonstrated that can reach the size scale of l/5 and even beyond, which is well suited for PNJ-based optical storage.…”
Section: Deep-subwavelength Fwhm and Neareld Effect Of Pnjsmentioning
confidence: 99%